Effect of flow path structure on electroosmotic dewatering - Tanaka, Takanori; Kato, Hiroki; Fujihara, Kenji; Jami, Mohammed Saedi; Iwata, Masashi (2014)
Empirical values of Epg for swelling clay and superabsorbent hydrogel lie between small and large pore models, suggesting some overlap of the double layers across the flow path of the materials. Based on Eq. (2), the electroosmotic dewatering is especially effective in removing liquid from highly compressible difficult-to-filter sludge, since it leads to a high electroosmotic pressure gradient.